#TITLE_ALTERNATIVE# - WAHYU ANTAR NUSA (NIM: 22013008), PEDRO
The geochemistry science is a branch of chemistry science that are used to solve various problems and to understand the Earth, and how the Earth works. Kutai Basin is bordered on the north by Mangkalihat high, Bengalon Fault Zone, and Sangkulirang. In southside it is bordering with Adang Fault Zone which acts as the axis of the basin of the zone since the end of the Paleogene. This research is done in Sanga-sanga Block in Kutai Basin wells T1, S1, L1, and B1 with target of Balikpapan Formation from the Middle Miocene. Geochemical analysis performed using Peter and Cassa parameters, include analysis of source rock maturity and richness. 1D modeling done to know about the burial history and the history of the maturity of the source rock on the research site. Compaction curve analysis is conducted to find out the value the erosion from each well using the method of normal compaction curve as a parameter of comparison. Analysis using normal compaction curve comparison metode to the well data obtained result of the erosion value of each well. Simple analysis performed to know how the last tectonic events specially which related to erosion, because the research area, regionally have had experienced uplifting event. Erosional calculation done on every wells using the compaction curve analysis. The basic usage of the compaction curve analysis is to calculate the erosion is normal compaction values of a layer that buried will reducing the porosity along with loading and depletion of inter-grain cavity (mechanical compaction), so the reduction value of the porosity can be presented in the form of diagrams of the compaction curve. Well compaction curve then compared to the compaction curve model to calculate the thick part that lost due to the erosion. The erosional that happened to the wells T1 is 1,939 feet, S1 is 2,625 ft, and L1 is 2,297 feet. Geochemical analysis in advance begins by validating the data, then the data will be inserted into the table that containing comparisons of geochemical values of the TOC, the Rock-Eval pyrolysis, and Ro against the depth. Calculation of the four wells results that the source rock in wells S1, T1, and L1 has entered the early mature window and becoming a potential source rock in the shale with the range of TOCÃ‚Â’s value begin from poor to excellent. Kerogen in Wells S1 and L1 is the kerogen type III (gas prone) formed at the transition of fluvio-deltaic environment and experienced the progradation to the eastward so that the loading process occurs at the western part first and then to the East part. The oil window maturity expected at 8,000-9,000 feet under L1, 10,000-11,000 feet under T1, and 7,000-8,000 feet under S1. The four wells i.e. T1, S1, L1, and B1 have mature value of Ro in the maturity level. Based on that data, the model of burial history and model of maturity history made up. The models gives an overview about the burial history and time of maturity of the wells. Maturity of T1 was happened on 12 Ma, S1 on 12.4 Ma, and L1 on 11.2 Ma which means the time of maturity begins before the last period of the tectonic that caused the petroleum system becoming very ideal because of the expulsion was happened earlier.